Exploratory data analysis of environmental governance at local level in the south-west region of Poland - Wiatkowska, Barbara (Eksploracyjna analiza ładu środowiskowego na poziomie lokalnym w południowo-zachodnim regionie Polski, 2018)
Conducting integrated measures within the framework of sustainable development requires an objective identification of the needs for their implementation based on the results of multifaceted analyses of many complex, interrelated factors reflecting the state of the natural environment and the economic and demographic situation. The increasing functionality of Geographic Information Systems (GIS), has made GIS databases a tool supporting the implementation of sustainable development activities. The aim of the study was to recognise the spatial variability of the level of environmental governance in the south-west region of Poland. Methods of research on multidimensional data mining techniques and geo-spatial analyses were applied, resulting in a theoretical model describing the regularities in the relationships between the analysed indicators of environmental governance. The level of environmental governance was most strongly determined by indicators concerning climate change and biodiversity
Biblioteka Regionalisty, 2018, Nr 18, s. 62-78
Keywords: environmental order; sustainable development; exploratory data analysis; spatial analysis; GIS; ład środowiskowy; zrównoważony rozwój; eksploracyjna analiza danych; analizy przestrzenne